Nevoid basal cell carcinoma syndrome: A clinical case report - Charu Girotra; Mayura Chande; Mukul Padhye; Gaurav Tomar; Aastha Maini (Elsevier, 2022)
Nevoid basal cell carcinoma syndrome (NBCCS) or Gorlin syndrome is a multi system disease exhibiting varied developmental abnormalities and a predisposition to neoplasms.A dentist may play a key role in early diagnosis of this disorder considering multiple & recurrent Odntogenic Keratocysts (OKC) are one of the first manifestations and are evident on routine X-rays.Present case report presents a patient diagnosed as NBCCS by clinical, radiographic and histological findings in a 13-year-old patient. We highlights the importance of early diagnosis of NBCCS which can help in preventive multidisciplinary approach to provide a better prognosis for the patient.